A Survey Study to Determine the Prevalence of Obesity Among Primary School Students in Baqubah District: Studi Survei untuk Menentukan Prevalensi Obesitas di Kalangan Siswa Sekolah Dasar di Distrik Baqubah - Ahmed , Amjad Adham; Al-Ezee , Ali Shakir; Ali , Abdulrahman Subhe (Indonesian Journal on Health Science and Medicine, 2025)
The current study aimed to know the prevalence of overweight and obesity rates among primary school children in Baquba district. The total number of samples was (105) samples (59 males and 46 females). The samples were obtained from children in primary schools from a special form prepared by the researcher that included (Sex, age, height, weight, mass, residence ). The results show that the number of overweight males is higher than the number of overweight females, as the number of males was 35 males, representing 59.32%, while the number of females was 24 females, representing 40.67%. The number of obese males is higher than the number of obese females, as the number of males was 32 males, representing 69.56%, while the number of females was 14 females, representing 30.43%. The results showed that the highest rate of overweight was among males living in the city, where the number of those infected was 23 males, and that the highest rate of obesity was among males living in the city, where the number of those infected was 21. We note that the lowest rate of infection was among females suffering from obesity living in the village, where the number of those infected was 4 females, representing 8.69%. Highlights: Higher overweight and obesity rates in males than females. Urban males have the highest overweight and obesity prevalence. Rural females have the lowest obesity rate (8.69%). Keywords: obesity , Overweight , primary schools